Antecedents of Job Satisfaction to Moonlighting Intentions Mediated by Organizational Commitment of Private Companies in Jakarta - Afandi, Irawan; Nilasari, B. Medina; Berliyanti, Dita Oki (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
This research aims to examine the influence of Moonlighting Intention and Personal Reasons on Job Satisfaction and Organizational Commitment, with a particular focus on the mediating role of Organizational Commitment. The study was conducted among employees working in private companies located in Jakarta, Indonesia. A total of 184 respondents participated, representing diverse educational backgrounds, working experiences, and demographic characteristics. The research applied a quantitative approach with data collected through a structured online questionnaire distributed via Google Forms, utilizing a cross-sectional survey design. Data were analyzed using descriptive statistics and hypothesis testing. The results indicate that Moonlighting Intention has a positive and significant impact on both Job Satisfaction and Organizational Commitment. However, Personal Reasons do not significantly influence Organizational Commitment or Job Satisfaction. Furthermore, Organizational Commitment shows a positive and significant effect on Job Satisfaction, but it does not function as a mediating variable between Moonlighting Intention or Personal Reasons and Job Satisfaction.These findings suggest that employees' intention to engage in additional jobs outside their primary employment does not necessarily reduce their organizational commitment or satisfaction levels. Conversely, personal motivations alone are insufficient to enhance employees’ commitment or satisfaction without organizational support. The study highlights the importance of strengthening organizational policies that foster employee engagement, loyalty, and satisfaction, particularly in the context of balancing external work activities and organizational responsibilities. The results contribute to the growing body of research on employee behavior in the private sector, providing valuable insights for organizational management to develop more effective human resource strategies